"A city coming into being": Walking in Berlin with Franz Hessel and Marshall Berman. Issue 5 (2nd November 2018) - Lisiak, Agata; Cox, Reece; Tienes, Flavia M.; Zbinovsky Braddel, Sophia
Abstract : This collaborative essay applies experimental walking and writing methods to address the experience of modernity in contemporary Berlin. Engaging critically with Marshall Berman's All That Is Solid Melts Into Air and using Franz Hessel's Walking in Berlin as our guide, we explore the city's scenes and sounds. Our reflections—some captured through photography, some expressed in prose—give way to essential questions: How does walking help us interrogate the experience of modernity? Can it help us understand what it means for Berlin (or any other city) to be "a city coming into being"? How do we make it come into being? Even when walking the same route, each person is bound to experience the city differently, and so we find it makes little sense to try to impose a single reading of contemporary Berlin. We invite the reader to walk through the city with us, but we do not insist on holding hands. Our text quite literally reflects various points of view on the city and should be considered a series of occurrences, reflections, and impressions that work both in contrast and concert. Walking a city produces countless readings, and our text aims to reflect that multiplicity: the reader may read it straight through, randomly, or hopscotch-style. If parts of the essay appear to be "melting into air, " this elusiveness reflects the experience of modernity which Berman wrote about and which we tried to also capture here. We hope that the format—collaborative, experimental, engaged, and open—will yield new reflections on urban modernities and open up new perspectives on urban theory and methods.